Influence of pre-slaughter transportation and stocking density on carcass and meat quality characteristics of Boer goats - Nikbin, Saeid; Panandam, Jothi Malar; Sazili, Awis Qurni (Taylor & Francis Group, 2016)
There are limited studies on the effects of transportation stress and stocking density under tropical conditions and their interactions with aging and muscle types on carcass and meat quality characteristics of goat. The present study investigated the effects of transportation and stocking density on carcass characteristics and meat quality traits of Longissimus dorsi, and Semimembranosus muscles in Boer goats. Thirty 1-year-old Boer goats, divided into two groups, were transported by road for 3.5 h, with density of 0.4 m2 and 0.2 m2 per animal, respectively; a third group which was not transported served as control. Meat pH, drip loss, cooking loss, tenderness and colour were measured from samples of the muscles. The transported goats had significantly lower carcass shrinkage, glycogen content, drip loss, tenderness, lightness, yellowness, hue-angle and chroma values compared to the non-transported group. In contrast, they showed significantly higher cooking loss and redness than the non-transported goats. Goats transported in high stocking density showed significantly (p < .05) higher live weight loss and lower dressing-out percentage than those in low stocking density. This study indicated that higher stocking density at pre-slaughter transportation increased shrinkage loss and deteriorated meat quality of goats. Therefore, using an appropriate density during transportation should be considered.